Pengaruh Kepuasan Pelanggan dan Kualitas Produk terhadap Minat Membeli Ulang Alat Pancing di Toko ACC Layang-layang dan Pancing Kelurahan Jepun Kabupaten Tulunggung - Afnandi, Khoimarul; Anasrulloh, Muhammad (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to determine: 1) the effect of customer satisfaction on repurchase intention, 2) the effect of product quality on repurchase intention, and 3) the simultaneous effect of customer satisfaction and product quality on repurchase intention among consumers at ACC Layang-layang and Fishing Equipment Store in Jepun Village, Tulungagung Regency. This research is a quantitative study using a descriptive approach. The sample consisted of 96 respondents selected using accidental sampling. Data were collected through a questionnaire. The results of the analysis show that: 1) partially, the t-count > t-table (5.596>1.985) and the significance value < 0.05 (0.000<0.05), indicating a significant effect of customer satisfaction on repurchase intention; 2) partially, the t-count > t-table (3.015>1.985) and the significance value < 0.05 (0.003 < 0.05), indicating a significant effect of product quality on repurchase intention; 3) simultaneously, the F-count > F-table (77.457>3.94) with a significance value of 0.000<0.05, indicating that customer satisfaction and product quality together have a significant effect on repurchase intention. The Adjusted R² value of 61.7% indicates that repurchase intention is influenced by customer satisfaction and product quality, while the remaining 38.3% is influenced by other variables not examined in this study.